Assessment of spatio-temporal dynamics of mangrove forest in Teluk Pangpang, Banyuwangi, East Java, Indonesia - ZAINUL HIDAYAH; HERLAMBANG AULIA RACHMAN; DWI BUDI WIYANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hidayah Z, Rachman HA, Wiyanto DB. 2024. Assessment of spatio-temporal dynamics of mangrove forest in Teluk Pangpang, Banyuwangi, East Java, Indonesia. Biodiversitas 25: 3138-3150. Mangrove forest in Teluk Pangpang, Banyuwangi District, East Java, Indonesia is located in a semi-enclosed bay area on the east coast of Java Island and bordering with Bali Strait. Since 2020, this location has been designated as an Essential Ecosystem Area (EEA) by the Indonesia Ministry of Environment and Forestry. Regardless of its designation as an EEA, information on vegetation stucture and spatio-temporal changes of Teluk Pangpang’s mangrove forest is limited. The availability of multi-temporal medium to high-resolution satellite imagery data enables researchers to monitor the condition of mangrove ecosystem using long-term data and reliable spatial continuity. The objective of this study is to investigate vegetation community structure of mangrove forest in Teluk Pangpang, as well as to determine the changes in extent and condition of mangrove forest measured as Mangrove Health Index (MHI) between 2015 and 2023 using remote sensing and GIS analysis. Spatio-temporal dynamics of MHI was determined using Sentinel-2 imagery data from 2015, 2018 and 2023. Meanwhile, a series of extensive survey in 15 transects with a total of 75 plots were conducted to obtain field data. The results showed that Rhizophora apiculata Blume and R. mucronata Lam. were the most important species with Important Value Index (IVI) of 140.91 and 148.24, respectively. Meanwhile, Sentinel-2 image processing results revealed a major increase in mangrove’s area, from 643.35 ha in 2015 to 737.51 ha in 2023. Furthermore, MHI analysis indicated improving conditions of mangrove ecosystem, as evidenced by the significant increased of mangroves area at the excellent MHI category (MHI>66.8) from 11.00 ha in 2015 to 175.86 ha in 2023. Based on Principal Component Analysis (PCA) several environmental parameters were strongly correlated to MHI including salinity, DO, TSS and mangrove’s diversity index. The findings of this study, primarily the application of MHI approach, may provide an alternative strategy for monitoring the dynamics of vegetation cover of mangrove forest in Teluk Pangpang and other mangrove areas in Indonesia.